2019
DOI: 10.1111/acfi.12490
|View full text |Cite
|
Sign up to set email alerts
|

Understanding participation in accounting standard‐setting: the case of AASB ED 192 Revised Differential Reporting Framework

Abstract: This paper explores the motives of participants in the standard‐setting process, based on the premise that standard‐setters strive for standards that are useful for decision‐making by a wide range of financial statement users. Our setting is the development of a contentious but contained Australian accounting standard, Reduced Disclosure Requirements. A consultative process initiated by the Australian Accounting Standards Board to create a specific Australian accounting standard for differential reporting prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…As the reviewed studies showed some gaps and disadvantages in the Conceptual Framework 2018, in this article it was decided to group all changes in the Conceptual Framework into four categories (RQ №2): a) filling gaps that existed before 2018 -in the -Filling gaps‖ group, b) clarification of uncertainties in past concepts (1989) or return them without any changes, which is assumed to be the main advantage of the Conceptual Framework IASB 2018 -in the -Clarifying‖ group, c) changed priority concepts -in the -Priority‖ group, d) updates that did not exist in none of the Conceptual Framework versions previously -in the -Updating‖ group. Fourth, the studied motives of the participants in the process of standard-setting (Handley et al, 2020) provide conclusions that this development process is managed by a certain elite close around the IASB. The exciting research made by Сade et al (2019) in terms of questions about an asset and a liability was found despite the data used by 2016.…”
Section: Prior Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As the reviewed studies showed some gaps and disadvantages in the Conceptual Framework 2018, in this article it was decided to group all changes in the Conceptual Framework into four categories (RQ №2): a) filling gaps that existed before 2018 -in the -Filling gaps‖ group, b) clarification of uncertainties in past concepts (1989) or return them without any changes, which is assumed to be the main advantage of the Conceptual Framework IASB 2018 -in the -Clarifying‖ group, c) changed priority concepts -in the -Priority‖ group, d) updates that did not exist in none of the Conceptual Framework versions previously -in the -Updating‖ group. Fourth, the studied motives of the participants in the process of standard-setting (Handley et al, 2020) provide conclusions that this development process is managed by a certain elite close around the IASB. The exciting research made by Сade et al (2019) in terms of questions about an asset and a liability was found despite the data used by 2016.…”
Section: Prior Literature Reviewmentioning
confidence: 99%
“…This is especially the case when some rules are not prescribed by IFRS, and national rules contradict international ones. Second, there is growing interest in the revised Conceptual Framework for financial reporting due to the consistent understanding by standard-setters and practitioners (Cordery and Sinclair, 2016); Tokar, 2018; Handley et al, 2020). The Conceptual Framework is the necessary foundation on which all IFRS accounting philosophy is built and is an integral part of standards.…”
Section: Introductionmentioning
confidence: 99%